High-grade pleomorphic rhabdomyosarcoma in a 60-year-old male: a case report and review of the literature. Issue 3 (3rd May 2020) - Taza, Fadi; Kanwal, Arjun; Zulty, Mary; Mustafa, Sadaf
ABSTRACT: Rhabdomyosarcoma is an aggressive malignant soft-tissue sarcoma that develop from undifferentiated mesenchymal cells. Less than 1% of all adult solid malignant cancers are sarcomas, and RMSs represent less than 2–5% of adult sarcomas.   RMS is divided into three main subtypes: Embryonal, alveolar and pleomorphic RMS (PRMS).   Most common subtype in adults is PRMS. Most common primary sites are extremities, trunk wall, and genitourinary organs. Metastasis are often found at diagnosis. 5-year overall survival rates were reported in the Surveillance, Epidemiology, and End Results database (SEER) to be 63% for pediatric patients and 27% for adults. Given the rarity of the adult PRMS, variation in its clinical presentation, characteristics of the tumor itself and the prognosis; there are very limited data available to guide the management of adults with PRMS. Herein we present a case report of pleomorphic rhabdomyosarcoma of the right thigh in a 60-year-old male who achieved a long-term survival (30 months) which was accomplished by multimodality treatment including surgery, radiotherapy, and chemotherapy.